Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3174145
|View full text |Cite
|
Sign up to set email alerts
|

Impact Activation Improves Rapid Button Pressing

Abstract: The activation point of a button is defined as the depth at which it invokes a make signal. Regular buttons are activated during the downward stroke, which occurs within the first 20 ms of a press. The remaining portion, which can be as long as 80 ms, has not been examined for button activation for reason of mechanical limitations. The paper presents a technique and empirical evidence for an activation technique called Impact Activation, where the button is activated at its maximal impact point. We argue that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 36 publications
(54 reference statements)
2
11
0
Order By: Relevance
“…So, while not intuitive, an increase in latency can lead to a reduction in the error rate. This illustration that the system's response can sometimes be too fast in a task involving participant anticipation of input timing replicates and theoretically extends the results of some studies previously reported upon [24,[27][28][29]. The model's assumptions about the effects of latency on the input distribution's µ and σ values were verified.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…So, while not intuitive, an increase in latency can lead to a reduction in the error rate. This illustration that the system's response can sometimes be too fast in a task involving participant anticipation of input timing replicates and theoretically extends the results of some studies previously reported upon [24,[27][28][29]. The model's assumptions about the effects of latency on the input distribution's µ and σ values were verified.…”
Section: Discussionsupporting
confidence: 82%
“…If the system response is faster than the user's anticipation, a non-intuitive conclusion follows: that latency must be increased for minimizing the discordance. This effect has recently been reported by several authors [24,[27][28][29]. In their studies, delaying the system response of the button-pressing reduced the user's error rate by 5-94%.…”
Section: Effects Of Latency On Anticipated-input Taskssupporting
confidence: 67%
See 2 more Smart Citations
“…However, as they use a Logitech G300 as reference mouse in all tests, whose absolute latency we report in this paper, absolute latencies for the other mice can be easily calculated. A commenter on rafalog, Chou Star, seems to have implemented a system that is quite similar to our LagBox 11 . They use the GPIO pin on a Raspberry Pi to toggle the electrical circuit of a mouse button while the mouse is connected to the Raspberry Pi.…”
Section: Input Latencymentioning
confidence: 99%